Reporting dream experience: Why (not) to be skeptical about dream reports - Windt, Jennifer M. (Frontiers in Human Neuroscience, 2013)
Are dreams subjective experiences during sleep? Is it like something to dream, or is it only like something to remember dreams after awakening? Specifically, can dream reports be trusted to reveal what it is like to dream, and should they count as evidence for saying that dreams are conscious experiences at all? The goal of this article is to investigate the relationship between dreaming, dream reporting and subjective experience during sleep. I discuss different variants of philosophical skepticism about dream reporting and argue that they all fail. Consequently, skeptical doubts about the trustworthiness of dream reports are misguided, and for systematic reasons. I suggest an alternative, anti-skeptical account of the trustworthiness of dream reports. On this view, dream reports, when gathered under ideal reporting conditions and according to the principle of temporal proximity, are trustworthy (or transparent) with respect to conscious experience during sleep. The transparency assumption has the status of a methodologically necessary default assumption and is theoretically justified because it provides the best explanation of dream reporting. At the same time, it inherits important insights from the discussed variants of skepticism about dream reporting, suggesting that the careful consideration of these skeptical arguments ultimately leads to a positive account of why and under which conditions dream reports can and should be trusted. In this way, moderate distrust can be fruitfully combined with anti-skepticism about dream reporting. Several perspectives for future dream research and for the comparative study of dreaming and waking experience are suggested.